Effect of electric field on dispersion of a solute in an MHD flow through a vertical channel with and without chemical reaction - Umavathi, J.C.; Kumar, Prathap J.; Gorla, Rama Subba Reddy; Gireesha, B. J. (Zielona Góra: Uniwersytet Zielonogórski)
The longitudinal dispersion of a solute between two parallel plates filled with two immiscible electrically conducting fluids is analyzed using Taylor`s model. The fluids in both the regions are incompressible and the transport properties are assumed to be constant. The channel walls are assumed to be electrically insulating. Separate solutions are matched at the interface using suitable matching conditions. The flow is accompanied by an irreversible first-order chemical reaction.
Keywords: Taylor dispersion; immiscible fluids; conducting fluid; MHD; chemical reaction